Characteristics and conflicts of interest at Food and Drug Administration Gastrointestinal Drug Advisory Committee meetings. - Rishad Khan (Public Library of Science (PLoS), 2021)
Introduction The United States Food and Drug Administration (FDA) Gastrointestinal Drug Advisory Committee (GIDAC) is involved in gastrointestinal drug application reviews. Characteristics and conflicts of interest (COI) in GIDAC meetings are not well described. This study analyzed FDA GIDAC meetings and characteristics that predict recommendations. Methods In this cross-sectional study, all publicly available GIDAC meetings where proposed medications were voted on were included. Data were collected regarding indications, medication sponsor, primary efficacy studies, and voting member characteristics (e.g. committee membership, COI). Univariate analyses were conducted at per-meeting and per-vote levels to assess for predictors of committee recommendation and individual votes respectively. Results Thirty-four meetings with 476 individual votes from 1998-2018 were included. Twenty-three (68%) proposals were recommended for approval and 25 (74%) received FDA approval. Most proposals involved >1 primary study (n = 27, 79%). At least one voting member had a COI in 24 (71%) of 34 meetings. Twelve (35%) meetings had at least one sponsor COI. Among 476 individual votes, 74 (15.5%) involved a COI, with 33 (6.9%) sponsor COI. COI decreased significantly over time, with fewer COI in 2006-2010, 2011-2015, and 2016-2020 compared to 1996-2000 and 2001-2005 (p<0.01). There were no significant associations between pre-defined predictors, including COI, and committee level recommendations or individual votes (p>0.05 for all univariate analyses). Conclusions The GIDAC reviewed 34 proposals from 1998-2018. The majority were recommended for approval and later approved by the FDA, highlighting the GIDAC's prominence in the regulatory process. COI are present among GIDAC panelists but decreasing over time and not associated with recommendations.